Mechanical analysis of wearable lower limb exoskeleton for rehabilitation - Wong, Zhen Yang; Ishak, Asnor Juraiza; Ahmad, Siti Anom; Chong, Yu Zheng (School of Engineering, Taylor’s University College, 2014)
This paper presents the mechanical analysis of a lower limb exoskeleton for rehabilitation for both legs that was developed in University Putra Malaysia (UPM). The main objective of the project is to develop a wearable exoskeleton system based on the average height of Malaysian to enhance the wearability of the system to lower limbs. An anthropomorphic design was adopted in the prototype with pneumatic actuations at the knee with one (1) degree of freedom (DOF), and ankle joints with two (2) DOFs via McKibben Pneumatic Artificial Muscle (MPAM). The prototype also mimics normal human joints range of motion (ROM) to enable movements similar to normal human gait patterns. Such anthropomorphic prototype was designed to fit users with different heights for both genders (male: 1.6$1.8 m, female: 1.5$1.7 m). As a result, the frame can be adjusted from 0.37$0.42 m for thigh segment and 0.385$0.445 m for lower leg segment. The actuation properties of MPAM also determined as well as Vertical Ground Reaction Force (VGRF) analysis to be performed to determine the performance of the prototype once integrated with actuation system and control system.